Oral feeding skills in premature infants: A concept analysis - Dyah Dwi Astuti; Yeni Rustina; Dessie Wanda (Belitung Raya Foundation, Indonesia, 2022)
Background: The delay in developing oral feeding skills becomes a problem experienced by premature infants. One of the reasons for the delay may be related to inconsistent definitions of oral feeding skills, which can cause discrepancies in the provision of nursing care. Objective: This study aimed to clarify the concept of oral feeding skills in premature infants. Methods: The Walker and Avant concept analysis method was used. A literature search was also conducted from five databases: CINAHL, PubMed, ProQuest, EMBASE, and Google Scholar, to find articles between January 2020 and December 2022. Results: The literature search obtained 20 articles on oral feeding skills from various disciplines. Five attributes were developed from the concept analysis, including (1) coordination ability to suck, swallow, and breathe, (2) the ability to regulate oral-motor functions, (3) the ability to regulate sensory functions, (4) the ability to maintain the stability of physiology function, and (5) the ability to regulate feeding behavior. Antecedents to oral feeding skills include immaturity of the nervous system, gestational age, feeding intolerance, increased length of stay and cost of care, increased rehospitalization, stress on parents, and increased morbidity and mortality. Consequences include optimization of growth and development, reduction of length of stay and cost of hospitalization, increased bonding attachment, increased self-efficacy of parents in caring for premature infants, and improvement of the quality of life of premature infants. Conclusion: The concept analysis provides five comprehensive attributes and their antecedents and consequences. However, this concept can be used to provide nursing care to premature infants, assess the criteria for discharge, and optimize nutrition for the growth and development of premature infants.